ANALISIS HUBUNGAN PASAR SAHAM INDONESIA DENGAN PASAR SAHAM BLOK BRICS SAAT TERJADI KRISIS - Muhammad Rummy Alfadjri; Buddi Wibowo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to identify the causal relationship between the Indonesian stock market and the stock markets of BRICS countries (Brazil, Russia, India, China, and South Africa) during the early period of the COVID-19 pandemic in 2020. The pandemic triggered global uncertainty and led to increased volatility in international financial markets, including Indonesia. Method: This quantitative research utilized secondary data comprising daily closing prices of stock indices: IHSG (Indonesia), BOVESPA (Brazil), RTS (Russia), BSE (India), SSE (China), and FTSE (South Africa), spanning from January to December 2020. These data were transformed into logarithmic daily returns. The analysis was conducted using the Granger causality test. Results: The results revealed a one-way causal relationship from the Brazilian and South African stock markets to the Indonesian market, a two-way relationship between the Russian and Indonesian markets, and no significant causality with the Indian and Chinese markets. These findings indicate that the Indonesian stock market is vulnerable to global market dynamics, especially those of the BRICS countries during crises. This research offers valuable insights for investors and policymakers in formulating risk management strategies.